An interview with Julia Kaye. Issue 1 (1st July 2019) - Murel, Jacob
Julia Kaye is a transgender cartoonist who recently published her first book Super Late Bloomer: My Early Days in Transition (Kaye 2018) with comics publisher Andrews McMeel. The book is a bound collection of select strips from her acclaimed web comic Up and Out. Though her web comic began as a run-of-the-mill gag strip, Up and Out transformed alongside Kaye herself into an autobiographical comic documenting her personal life as a transgender woman. Super Late Bloomer is comprised from a selection of these daily, autobiographical strips that document Kaye's first months in hormone transition. The book was published in May 2019 and was acclaimed by reviewers. It presents a new format for the currently in vogue graphic memoir movement, a comics diary, an autobiographical collection comprised of quotidian, piecemeal installments from the artist's daily experience. Kaye currently lives in Los Angeles where she works for Disney on the television show Big City Greens (2018–9) and continues to update her web comic Up and Out.